Evaluación del efecto de diferentes sustratos y dos tipos de ambientes en el comportamiento agronómico de cannabis sativa, en el Campus Salache – UTC, cantón Latacunga, provincia de Cotopaxi 2022. - Curicho Yasi, Kety Carolina (2022)
The present investigation was carried out at the Technical University of Cotopaxi, its main objective was to evaluate the effect of different substrates and two types of environments on the agronomic behavior of Cannabis sativa, at the Salache - UTC campus, Latacunga canton, Cotopaxi province, 2022, the optimal substrate for the growth and development of Cannabis sativa was determined, therefore, bibliographic information regarding the research was collected. In the same way, the most suitable environment for the growth and development of the same was identified. In this regard, a completely randomized block design (DBCA) was carried out, with 8 repetitions in two environments, therefore the following variables were taken: height, number of leaves and number of branches, a Tukey test of significance was used. 0.05% with which the treatment and the optimal environment for the development of Cannabis sativa were determined, which was obtained as a result, environment 1 + T1 (gravel 30%, vermiculite 25%, compost 25% and black earth at 20 %) with a height of 55.5 cm at 120 days, followed by environment 1 + T3 (perlite 30%, swamp peat 25%, trichoderma 25% and black earth 20%) with a height of 53.63cm at 120 days. In the same way, it is recommended to implement the cultivation of Cannabis sativa in the open field because the cultivation had an optimal development, and it adapted to the existing climatic variability in the province of Cotopaxi.